Mechanisms of plant growth and improved productivity : (M. Dekker, 1994)
Details current knowledge of the mechanisms of plant growth and productivity and describes state-of-the-art techniques to isolate, characterize, and manipulate specific plant genes in order to enhance plant productivity. DLC: Crops - Growth.